2003
DOI: 10.2190/4wjb-bw16-2tge-565w
|View full text |Cite
|
Sign up to set email alerts
|

Child Mental Health in Latin America: Present and Future Epidemiologic Research

Abstract: Future research needs to focus on understanding of resilience and formal and informal mental health delivery systems of care available in different Latin American countries. Such research has high potential for ameliorating the prevention and treatment of child and adolescent mental health problems in this region of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 71 publications
0
22
0
15
Order By: Relevance
“…There is a scarcity of epidemiological studies on mental disorders in children in low- and middle-income countries [6, 810]. A systematic review of population-based samples from low- and middle-income countries found that the prevalence of mental disorders varied between 10 and 20 % among children and adolescents [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is a scarcity of epidemiological studies on mental disorders in children in low- and middle-income countries [6, 810]. A systematic review of population-based samples from low- and middle-income countries found that the prevalence of mental disorders varied between 10 and 20 % among children and adolescents [6].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos longitudinais internacionais indicam que existe uma continuidade dos problemas de saúde mental na infância, na adolescência e na vida adulta, sendo que a maioria das pessoas diagnosticadas tardiamente já apresentavam sintomas precoces, o que justifica a importância dos estudos epidemiológicos voltados para a identificação de dificuldades relativas à saúde mental infantil, considerando que causam estresse duradouro na vida dos indivíduos e demais grupos envolvidos -família, escola e comunidade 1,7,8 . Com o objetivo de levantar e analisar os estudos populacionais de saúde mental infantil e do adolescente realizados na América Latina no período de 1980 a 1999 e buscando compreender como a demanda das crianças e adolescentes que apresentam problemas de saúde mental na região é atendida, Duarte et al 7 encontraram dez estudos, realizados em seis países diferentes que empregaram algum tipo de método de amostragem aleatória e utilizaram instrumentos padronizados de avaliação.…”
unclassified
“…Com o objetivo de levantar e analisar os estudos populacionais de saúde mental infantil e do adolescente realizados na América Latina no período de 1980 a 1999 e buscando compreender como a demanda das crianças e adolescentes que apresentam problemas de saúde mental na região é atendida, Duarte et al 7 encontraram dez estudos, realizados em seis países diferentes que empregaram algum tipo de método de amostragem aleatória e utilizaram instrumentos padronizados de avaliação. Em geral, foi encontrado um padrão semelhante de prevalência e fatores de risco para problemas de saúde mental em crianças e adolescentes nos países latino-americanos.…”
unclassified
“…Kohn, Vicente, Saldivia, Rioseco, and Torres (2008) talked about psychiatric morbidity among the Chilean geriatric population. Moreover, there is a productive core/ nucleus at the University of Sao Paulo in Brazil (Andrade et al, 2003;Duarte et al, 2003;De Toledo Piza Peluso and Bay, 2004;Andrade, Viana, Tó foli, & Wang, 2008;Mercadante, Evans-Lacko, & Paula, 2009) who carry out multicentric and multinational research and which has maintained its scientific leadership.…”
Section: Epidemiological Research In Latin Americamentioning
confidence: 99%